Case report: Sintilimab combined with anlotinib as neoadjuvant chemotherapy for metastatic bone tumor resection in patients with PSC - Bao, Zheming; Yu, Xiuchun; Zheng, Kai; Zhai, Kai; Cui, Haocheng; Xu, Ming (Frontiers in Immunology, 2024)
Case summary: A 69-year-old male diagnosed with malignant bone tumor in the proximal femur was admitted to our hospital in June 2022 with recurrent fever as well as swelling and pain in the left thigh for twenty days. The initial computed tomography (CT) scan of the chest showed a pulmonary cavity (20 mm × 30 mm) and scattered lung masses. Subsequently, he underwent a CT-guided needle biopsy to distinguish the essence of osteolytic bone destruction and soft tissue mass in the left proximal femur which showed metastatic sarcomatoid carcinoma histology. Genetic testing revealed TERT c.-124C mutation (abundance 8.81%), TP53 p.R342 mutation (abundance 11.35%), tumor mutational burden (TMB) 7.09 muts/Mb, microsatellite stability (MSS), and PD-L1 (SP263) TPS 5% were also detected. The patient was tentatively treated with a combination of antiangiogenic drug and PD-1 inhibitor. After one course, the tumor volume significantly reduced in magnetic resonance imaging (MRI) and pathological fracture occured in the femur after combined treatment. The patient received proximal femoral tumor resection and prosthesis replacement after defervescence. Sequentially sintilimab with anlotinib were administered for over 1 year. Finally, the local tumor was well controlled, and no obvious drug-related adverse reactions were observed. The lesions in the lung remained in partial response (PR) for more than 16 months and complete response (CR) of metastatic tumor in the proximal femur was observed through imaging examinations.Conclusion: This is the first reported case of a metastatic PSC in femur showing a favourable response to the treatment consisting of anlotinib combined with sintilimab. This case suggests that antiangiogenic therapy combined with immunotherapy may benefit patients with metastatic PSC in the preoperative adjuvant therapy for limb salvage.